English Lecturers’ Digital Literacy and Their Scientific Publication: Seeking the Correlation - Veni Roza (Lingua Cultura, 2021)
The research aimed at seeking the correlation between English lecturers’ digital literacy and their productivity in publishing their research articles. It applied a quantitative research by correlating the variables between the online questionnaire result of English lecturers’ digital literacy and lecturers’ scientific publication data from their Google Scholar accounts and Science and Technology Index Portal or SINTA Portal of the Republic of Indonesia. The research population was all permanent English lecturers at State Islamic Higher Education in West Sumatera. There were 65 respondents in three institutions, but only 85% of participants gave feedback on the online questionnaire. The questionnaire was about the digital literacy of English lecturers in using and finding digital information and technology. The research also accounted online journal publication of each English lecturer in his/her account. To analyze the data, the research used the Pearson correlation formula. The finding reveals a positive correlation between English lecturers’ digital literacy and their research publication, as shown by the Pearson correlational coefficient, 0,48. The score lies between 0,40-0,59, which is under sufficient category. The result implies that English lecturers’ digital literacy has something to do with publication. The more digitally literate they are, the more productive they will be, even though there are other factors that influence someone to carry out the publication.